'But ... Would I Be Able to Toast With Friends?' When Service Users Ask for New Care Pathways - Michele Rocelli; Ludovica Aquili; Arianna Palmieri; Diego Romaioli; Lea Ferrari; Elena Faccio (Wiley, 2024)
ABSTRACT Introduction The WHO European Mental Health Action Plan (2013-2030) emphasises the need to generate services that are more inclusive and attentive to the co‐construction of care practices. This exploratory research investigates the needs of young substance abusers shown during their stay in residential communities; in particular, it explores the idea that treatment may include a new phase focused on how to manage moderate or controlled alcohol intake during residential care. Interviews with young ex‐users open up critical reflections on complete abstinence programmes from all substances, including alcohol, as a prerequisite for discharge and also provide examples of how to co‐design a plan for mindful drinking. Methods Fourteen young adults, aged 19-32 years, non‐alcoholists, treated at rehab in Fermo, in central Italy, were interviewed during a programme between 6 and 18 months of period. They were asked about exploring needs in preparation for the conclusion of the rehabilitation pathway. From this exploration emerged the need to introduce controlled alcohol intake during the rehabilitation stay. This request became the focus of the semi‐structured interviews. Results Three main themes emerged, which are as follows: (1) difficulties in integrating the new identity with the past of consumption, (2) resistance to the idea of total abstinence in social relations and (3) uncertainties about post‐community behaviour regarding alcohol intake. At the same time, three unexpected needs were expressed: (1) test the personal knowledge and skills on how to manage the alcohol intake, (2) receive support during the residential path to build up self‐control competence given the post‐discharge period and (3) build a personalised therapeutic path together with the supervisor and the operators while still at the rehab, according to the realistic lifestyle and routine outside the rehab. Conclusions This research highlights the importance of personalising treatment based on each user's needs, going far beyond the standardised treatments for users previously considered unable of self‐control and self‐determination. For that purpose, the relationship between the users and the operators might be privileged, as it is able to cover the specific needs aimed for the new identity. Involving the Participants The research sparked a discussion within the community, involving and initiating an open dialogue between the operators and the users, allowing them to focus on certain innovative strategies offered by the service, putting the users' needs at the very centre of the attention. The results were compared and discussed actively with the participants involved.